2015
DOI: 10.1063/1.4919242
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability and defect energetics of ZnO from diffusion quantum Monte Carlo

Abstract: ABSTRACT:We have applied the many-body ab-initio diffusion quantum Monte Carlo (DMC) method to study Zn and ZnO crystals under pressure, and the energetics of the oxygen vacancy, zinc interstitial and hydrogen impurities in ZnO. We show that DMC is an accurate and practical method that can be used to characterize multiple properties of materials that are challenging for density functional theory approximations. DMC agrees with experimental measurements to within 0.3 eV, including the band-gap of ZnO, the io… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 118 publications
3
72
0
Order By: Relevance
“…In fact, recent calculations have shown that a 12.5% of Fock exchange is necessary to reproduce the band gap of stoichiometric TiO 2 rutile and anatase polymorphs, whereas within the HSE type of functional it is necessary to reduce it to 20% . Similar findings have been also recently reported for ZnO including very accurate diffusion quantum Monte Carlo calculations . This fact seems to be a consequence of the different dielectric constant of each material and, in fact, several authors suggested to use this property to define the amount of Fock exchange required to properly describe a given solid, although one needs to realize that such approach includes, in an empirical way, a macroscopic parameter external to theory, even if this can be done in a self‐consistent manner …”
Section: Models and Methodsmentioning
confidence: 59%
“…In fact, recent calculations have shown that a 12.5% of Fock exchange is necessary to reproduce the band gap of stoichiometric TiO 2 rutile and anatase polymorphs, whereas within the HSE type of functional it is necessary to reduce it to 20% . Similar findings have been also recently reported for ZnO including very accurate diffusion quantum Monte Carlo calculations . This fact seems to be a consequence of the different dielectric constant of each material and, in fact, several authors suggested to use this property to define the amount of Fock exchange required to properly describe a given solid, although one needs to realize that such approach includes, in an empirical way, a macroscopic parameter external to theory, even if this can be done in a self‐consistent manner …”
Section: Models and Methodsmentioning
confidence: 59%
“…The optimized pseudopotentials presented here have also been employed in a few recent studies of bulk transition metal oxides [65][66][67] as well as bulk metals 65,68 . For comparison with our dimer results, we reproduce the bulk data in Table IV with permission of the authors.…”
Section: Comparison With Bulk Studiesmentioning
confidence: 99%
“…In principle, quasiparticle calculations provide a more accurate description, 33,34 but these are computationally intensive and are based on geometries that are obtained with DFT. 35,36 Quantum Monte Carlo calculations [37][38][39] can also provide a direct solution to the many-body problem, but applications to defects have been limited due to the computational complexity.…”
Section: Introductionmentioning
confidence: 99%